Immunity-based accommodation of aircraft subsystem failures. Issue 1 (3rd January 2017) - Togayev, Adil; Perhinschi, Mario; Moncayo, Hever; Al Azzawi, Dia; Perez, Andres
Abstract : Purpose: This paper aims to describe the design, development and flight-simulation testing of an artificial immune-system-based approach for accommodation of different aircraft sub-system failures/damages. Design/methodology/approach: The approach is based on building an artificial memory, which represents self- (nominal conditions) and non-self (abnormal conditions) within the artificial immune system paradigm. Self- and non-self are structured as a set of memory cells consisting of measurement strings, over pre-defined time windows. Each string is a set of features values at each sample time of the flight. The accommodation algorithm is based on the cell in the memory that is the most similar to the in-coming measurement. Once the best match is found, control commands corresponding to this match are extracted from the memory and used for control purposes. Findings: The results demonstrate the possibility of extracting pilot compensatory commands from the self/non-self structure and capability of the artificial-immune-system-based scheme to accommodate an actuator malfunction, maintain control and complete the task. Research limitations/implications: This paper concentrates on investigation of the possibility of extracting compensatory pilot commands. This is a preliminary step toward a more comprehensive solution to the aircraft abnormal condition accommodation problem. Practical implications: The results demonstrate the effectiveness of the proposed approach using a motion-based flight simulator for actuator and sensor failures. Originality/value: This research effort is focused on investigating the use of the artificial immune system paradigm for control purposes based on a novel methodology.